P‐13: The Relationship Between Crystallinity and Device Characteristics of In‐Sn‐Zn‐Oxide. Issue 1 (June 2015) - Nonaka, Yusuke; Takasu, Takako; Ishihara, Noritaka; Oota, Masashi; Ishiguro, Yoshimi; Kurosawa, Yoichi; Dairiki, Koji; Yamazaki, Shunpei
Abstract : We have reported that the transistors having the c‐axis‐alignedcrystalline (CAAC) In‐Ga‐Zn‐oxide show good performance. For In‐Sn‐Zn‐oxide, we investigated relation between crystallinity and electrical properties. The experimental results suggest that In‐Sn‐Zn‐oxide can have a layered structure like a CAAC structure, and their high crystallinity improves device performance.